Coordination Between the Indonesian Food and Drug Authority Regional Office in Palangka Raya and J&T Express Palangka Raya in Tackling the Distribution of Frequently Misused Certain Drugs in Central Kalimantan - Marzio, Aldy (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This paper aims to explain the coordination process between the Indonesian Food and Drug Authority Regional Office in Palangka Raya (BBPOM Palangka Raya) and J&T Express Palangka Raya in tackling the distribution of Certain Drugs Frequently Misused (Obat-Obat Tertentu/OOT) in Central Kalimantan, as well as to conduct a SWOT analysis of the coordination. The findings indicate that the coordination between BBPOM Palangka Raya and J&T Express Palangka Raya was initiated through the activity titled “Strengthening Cooperation between BBPOM Palangka Raya, ASPERINDO, and Courier Service Companies,” held on September 12, 2022. Throughout 2023, BBPOM Palangka Raya and J&T Express Palangka Raya collaborated in seizing and opening packages suspected of containing OOT to obtain information regarding the types of products and the identities of the senders and recipients. Laboratory tests were also conducted to verify the OOT products' contents in these parcels. The coordination represents a form of vertical coordination, influenced by mutual awareness, effective communication, clear division of tasks, and discipline. Although the coordination has strengthened oversight, BBPOM Palangka Raya remains dependent on the Directorate of Food and Drug Intelligence of BPOM for information regarding the shipment of packages containing OOT. This coordination also presents opportunities for public outreach and training for other courier service companies and the development of a technology-based monitoring system. However, the distribution of OOT may evolve into more complex and less detectable methods. Furthermore, budget efficiency policies may challenge BBPOM Palangka Raya in effectively coordinating with J&T Express Palangka Raya.